We Do Not Worship Buddha Images: Buddhist Response to Religious Bullying in Online Media (Religion, Culture, and State Journal, 2022)
The stereotyping view of radical Islamic groups manifested in verbal violence against other religious groups is increasingly growing freely along with the expansion of public communication spaces in cyberspace. This has made it even more frustrating for people of other religions to respond to this bullying. Religious minorities, such as Buddhists, also use information technology to express responses to negative stereotypes. In Indonesia, Buddhism often gets a negative impression because it is considered as "idol worship", something which for Muslims, as the majority group, is the biggest sin. This mistaken view of Buddhists has not only resulted in a bad view of Buddhists, but has led to violence as evidenced by the case of lowering the Buddha statue in TanjungBalai. Buddhists who are based on the moral teachings of self-control try not to give a negative response that is reactive, but they appear increasingly progressive in spreading the â€œright viewâ€ of their teaching principles so that they are no longer misunderstood and become objects of discrimination. Apart from being in the form of lectures disseminated in online media, efforts to provide religious literacy education are also conveyed through short stories and popular songs. Through content analysis, this paper will describe various ways of public communication of Buddhists to overcome negative stereotyping about them, especially the perception of being "idolaters". Also see to what extent the effectiveness of this monologue-impressed communication is conveyed to those who bully.
Keywords: counter radicalism; digital Buddhism; public communication; religious literacy